Dampak Pandemi Covid-19 Terhadap Pendidikan Serta Kaitannya Dengan Andragogi Kurikulum Merdeka Dalam Rangka Perkembangan Pendidikan - Muliadi , Erlan; Zakaria, Muh. (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi NW Pancor, 2023)
This journal reviews the phenomenon of the occurrence of Covid-19 which has sparked major changes in the world of education, namely changes in the learning process from face to face learning to online learning. The online learning process in the Covid era was manifested so that the learning process was not hampered and continued to run well and regularly. Even though Covid-19 has brought a way of learning with a different process and innovating, new things like this also sometimes don't match the results of their performance with what you want. The Covid-19 pandemic has led to a learning loss which is not the same in terms of acquiring student competencies and learning crises. So the existence of independent curriculum andragogy is an effort to restore the learning process by the Ministry of Education, Culture, Research and Technology (KEMENDIKBUDRISTEK) to overcome educational problems during Covid-19. The purpose of making this article is to find out how the independent curriculum carries out its role in overcoming problems that occur in the process of implementing education due to the covid that hit. The type of research used is to use a literature study approach research method. Literature study is used because in this study it examines and studies materials from library data. The source of data from this study is from journals that describe the problem of being studied. The data analysis technique used to draw conclusions is inferential, namely a way of drawing conclusions from general things to specific things.